Development of perovskite-based light emitting diodes with improved stability 1.0 - Sim, Zong Huan (2019)
The discovery of organic-inorganic lead halide perovskite luminating under ultraviolet excitation and its excellent optoelectronic properties led to the increased in studies of the fundamental understanding and its potential application. As such, more researches were invested in manufacturing at a low cost and at a larger scale for industrial applications. In this report, the synthesis of colloidal cesium-lead halide (CsPbX3) perovskite NCs via microwave irradiation were discussed. The stability of the perovskite NCs were improved by varying the combination of halide ions and the type of capping ligands (oleic acid and stearic acid) used. Characterisation of the perovskite NCs were made by measuring its absorbance and fluorescence intensity. These synthesized perovskite NCs were subjected to thermal degradation and its fluorescence intensity were measured. The rate of decrease in intensity indicates the stability of the NCs. Quantum yield was further calculated using the sample and a reference compound for a more quantitative characterisation. The stearic acid (SA)-capped having higher melting point property reduces tendency of SA leaving the crystal surface, preventing aggregation between perovskite NCs and improving its stability as compared to oleic acid (OA)-based.